1992
DOI: 10.1021/j100197a027
|View full text |Cite
|
Sign up to set email alerts
|

Ab initio studies of hydrogen bonding of N-methylacetamide: structure, cooperativity, and internal rotational barriers

Abstract: Hydrogen bonding interactions and their effect on the structure and the energetics of the rotation about N-Cu and Cu-C' bonds are studied for N-methylacetamide (NMA) by use of ab initio quantum mechanical calculations. The structure and methyl rotational barriers for isolated NMA have k e n determined at the Hartree-Fock (HF) level with 6-31G. 6-31G*, and 6-31 1G** basis sets and at the second-order Mdler-Plesset perturbation (MP2) level with a 6-31G* basis set including geometry optimization for the different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
170
0
3

Year Published

1998
1998
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 198 publications
(188 citation statements)
references
References 13 publications
15
170
0
3
Order By: Relevance
“…Although there already exist a number of literatures on ab initio studies of NMA-water complexes, [54][55][56][57][58][59] most of the previous works concerned about H-bond energies, optimized structures, and amide I mode frequency. Guo and Karplus showed that a single NMA molecule has three H-bonding sites (denoted as A, B, and C) as shown in Figure 1.…”
Section: Ab Initio Calculation Results For Nma-h 2 O and Nma-d 2 O Comentioning
confidence: 99%
See 1 more Smart Citation
“…Although there already exist a number of literatures on ab initio studies of NMA-water complexes, [54][55][56][57][58][59] most of the previous works concerned about H-bond energies, optimized structures, and amide I mode frequency. Guo and Karplus showed that a single NMA molecule has three H-bonding sites (denoted as A, B, and C) as shown in Figure 1.…”
Section: Ab Initio Calculation Results For Nma-h 2 O and Nma-d 2 O Comentioning
confidence: 99%
“…Guo and Karplus showed that a single NMA molecule has three H-bonding sites (denoted as A, B, and C) as shown in Figure 1. 54 Using the Gaussian 98 program, 60 we obtained the optimized geometry of NMA-H2O(A) complex at the RHF/6-311++G** level, where the H-bond distance rA (see Fig. 1) is found to be 1.9785 Å.…”
Section: Ab Initio Calculation Results For Nma-h 2 O and Nma-d 2 O Comentioning
confidence: 99%
“…It is a nontrivial problem to choose a small hydrogen bonded dimer that accurately represents hydrogen bonds found in protein side chains and main chains. Formamide, acetamide, N-methylacetamide (NMA), formamide-formaldehyde, and water dimers (and combinations thereof) have been explored in the literature, primarily with the purpose of identifying various local and global minima in a given complex (9,10,(17)(18)(19)(20)(21)(22)(23). Although NMA dimers are routinely used to model main-chain hydrogen bonds, the methyl groups on both ends can contribute significantly to the dimerization energy surface (13,21), and hence formamide is a better model for amino acid side-chain hydrogen bonds.…”
Section: Methodsmentioning
confidence: 99%
“…These effects are here assumed to yield independent and additive shifts of the amide I frequency from the gas phase value ω NMA = 1723 cm −1 of unperturbed, uncoupled NMA, [47][48][49] which has been extensively studied as a model compound of a peptide unit. 31,[50][51][52][53][54][55][56][57] The intrinsic frequency of the amide I oscillator in residue i can thus be described as…”
Section: Amide I Band Calculationmentioning
confidence: 99%